Recent advances of PVA-based hydrogels in cartilage repair application - Heng Li; Chengwei Wu; Xiaogang Yu; Wei Zhang (Journal of Materials Research and Technology, 2023)
Articular cartilage is critical for knee joint motion as a connective tissue to disperse loads and resist high-stress loadings. However, due to the lack of vascular, neural, and lymphatic tissues, the self-repair capacity of cartilage is fairly poor. Traditional clinical therapies including palliative and surgical treatments, have improved pain relief and defect filling, yet limitations such as immune rejection and fibrocartilage formation still exist. Therefore, it is a key concern to develop new approaches and materials for cartilage repair. Physically crosslinked polyvinyl alcohol (PVA) hydrogels possessing viscoelastic properties and excellent biocompatibility have become promising candidate materials for cartilage repair. Nevertheless, great improvements can still be made in terms of the mechanical, microstructural, and biological properties of the hydrogels. In this paper, we first summarize the basic properties and preparation methods of PVA hydrogels. Then, in the context of cartilage repair, an overview of recent advances in the improvement of the mechanical properties, structural design, and bioactivity of physically crosslinked PVA hydrogels is presented. Finally, we discuss the challenges and future trends in the development of PVA hydrogels for cartilage and osteochondral repair applications.